Comparion of different POS tagging technique (N-Gram, HMM and Brill's tagger) for Bangla - Hasan, Fahim Muhammad; Naushad UzZaman; Khan, Mumit (BRAC University, 2010)
Includes bibliographical references (page 6-7).